2021
DOI: 10.1101/2021.10.07.21250296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary Manipulation of the Gut Microbiome in Inflammatory Bowel Disease Patients: Proof of Concept

Abstract: Diet is a modifiable, non-invasive, inexpensive behavior that is crucial in shaping the intestinal microbiome. A microbiome imbalance or dysbiosis in inflammatory bowel disease (IBD) is linked to inflammation. Here, we aim to define the impact of specific foods on bacterial species commonly depleted in patients with IBD to better inform dietary treatment. We performed a single-arm, pre-post intervention trial. After a baseline period, a dietary intervention with the IBD-Anti-Inflammatory Diet (IBD-AID) was ini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 117 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Having a systematic process for integrating diet assessment and discussion into the routine visit should increase the likelihood that the diet conversation will occur. This is important given that less than 50% of PCPs currently broach this conversation, despite the recommendations of public health and professional nutrition organizations 11,13-15. The comments made by staff support the feasibility of seamlessly integrating a brief diet assessment and discussion into routine primary care visits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Having a systematic process for integrating diet assessment and discussion into the routine visit should increase the likelihood that the diet conversation will occur. This is important given that less than 50% of PCPs currently broach this conversation, despite the recommendations of public health and professional nutrition organizations 11,13-15. The comments made by staff support the feasibility of seamlessly integrating a brief diet assessment and discussion into routine primary care visits.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these recommendations, most PCPs do not routinely address diet or only discuss it in the context of obesity 13. The National Health and Nutrition Examination Survey, 2011-2018 found that fewer than one-third of providers advised their patients on diet, with persons identified as obese or overweight targeted for diet advice 13. The need for diet advice is most often determined by body weight, body mass index, or lab tests, rather than actual food intake.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations